2021
DOI: 10.1108/jarhe-08-2020-0263
|View full text |Cite
|
Sign up to set email alerts
|

A capability maturity model for assessment of active learning in higher education

Abstract: PurposeAlthough active learning methodologies are recognized as an effective means to achieve expected educational demands, in practice, the teaching and learning processes are still widely characterized by traditional pedagogy aspects. As a result, teaching innovations in science, technology, engineering and math (STEM) education are carried out in isolation in specific disciplines, programs or departments. To addresses these challenges and to stimulate useful teaching innovations, this study aims to propose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 77 publications
0
10
0
Order By: Relevance
“…HEIs considered as complex organizations because it has different interests and needs different strategies where models of maturity can contribute to the future of learning practices (Duarte and Martins, 2013). Therefore, Garbin et al (2021) suggested a capability maturity model (CMM) to assess the maturity level of active learning practices and enhance the performance of HEIs. In addition, Llamosa-Villalba and Méndez Aceros (2010) proposed a processes management model to bring a systematic benchmarking of organizational, logistical, tactical, operational processes and training programs for HEIs.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…HEIs considered as complex organizations because it has different interests and needs different strategies where models of maturity can contribute to the future of learning practices (Duarte and Martins, 2013). Therefore, Garbin et al (2021) suggested a capability maturity model (CMM) to assess the maturity level of active learning practices and enhance the performance of HEIs. In addition, Llamosa-Villalba and Méndez Aceros (2010) proposed a processes management model to bring a systematic benchmarking of organizational, logistical, tactical, operational processes and training programs for HEIs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…HEIs considered as complex organizations because it has different interests and needs different strategies where models of maturity can contribute to the future of learning practices (Duarte and Martins, 2013). Therefore, Garbin et al (2021) suggested a capability Bickers (1993) conducted analyses to enhance the admissions process through PM approaches. Moreover, Yerk-Zwickl (1995) studied the information system development with project management method at higher educational institutions.…”
Section: Project Management In Higher Education Institutionsmentioning
confidence: 99%
“…The aspects of "teaching and learning processes" and "evaluation methods" are related to the key elements of "Process management" and "support", respectively. According to Garbin et al (2022), teaching and learning processes and evaluation methods can be organized along the five maturity levels (initial, replicable/ repeatable, defined, management and optimized). Evolution from maturity level initial to the optimized level may occur gradually on time, advancing through intermediary levels.…”
Section: Convergence Of Maturity Model Education and Evaluation In Ac...mentioning
confidence: 99%
“…responsibility of teaching and learning. In the area of "evaluation methods," it may be at Level 4 (managed), characterized by courses evaluated by the higher education institutes concerning active methodologies, and expanding alternative ways to assess the levels of learning and skills to more than one course (Garbin et al, 2022).…”
Section: Maturity Model Education and Evaluationmentioning
confidence: 99%
See 1 more Smart Citation